2009
DOI: 10.1371/journal.pone.0005356
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondrial A10398G Polymorphism, Interaction with Alcohol Consumption, and Breast Cancer Risk

Abstract: Polymorphisms in the mitochondrial genome are hypothesized to be associated with risk of various diseases, including cancer. However, there has been conflicting evidence for associations between a common polymorphism in the mitochondrial genome (A10398G, G10398A in some prior reports) and breast cancer risk. Reactive oxygen species, a by-product of mitochondrial energy production, can lead to oxidative stress and DNA damage in both the mitochondria and their cells. Alcohol consumption, which may also lead to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 24 publications
0
42
0
Order By: Relevance
“…For example, the reported prevalence rate of alcohol drinking among Chinese female had increased from 2.58% in 1993 (PRC, 1995) to 4.5% in 2002 (Ma et al, 2005) (Yu et al, 1995) and estrogen (Taioli et al, 1996) had also been reported to affect the relationship between alcohol drinking and breast cancer in different ethnics. For example, 10398G allele in the mitochondrial genome was reported to influence the alcohol metabolism, which may also modify the association between alcohol drinking and breast cancer (Pezzotti et al, 2009). Additionally, consistent J-shaped curve of alcohol drinking on the risk of diseases was found in many cardiovascular diseases (White et al, 1999;Gmel et al, 2001).…”
Section: Discussionmentioning
confidence: 96%
“…For example, the reported prevalence rate of alcohol drinking among Chinese female had increased from 2.58% in 1993 (PRC, 1995) to 4.5% in 2002 (Ma et al, 2005) (Yu et al, 1995) and estrogen (Taioli et al, 1996) had also been reported to affect the relationship between alcohol drinking and breast cancer in different ethnics. For example, 10398G allele in the mitochondrial genome was reported to influence the alcohol metabolism, which may also modify the association between alcohol drinking and breast cancer (Pezzotti et al, 2009). Additionally, consistent J-shaped curve of alcohol drinking on the risk of diseases was found in many cardiovascular diseases (White et al, 1999;Gmel et al, 2001).…”
Section: Discussionmentioning
confidence: 96%
“…Mt-polymorphisms pinpointed for increased risk were: G9055A, A10398G, and T16519C, whereas T3197C and G13708A lowered the risk for breast tumors. In a provocative study recently reported by Pezzotti et al [2009] on a series of 1,561 breast cancer cases and 2,209 matched controls of predominantly European-American ancestry, the authors observed an interaction between breast malignancy, alcoholism, and A10398G allele. The combination of this allele with augmented alcohol consumption produced 56% increased risk for breast cancer with regard to the risk shown by non-drinking females carrying the same variant.…”
Section: Inherited Mt-mutations and Cancermentioning
confidence: 93%
“…In humans, several studies have shown a relatively high frequency of mtDNA mutations in breast tumor tissues (range 20%-93%) . Among them, we have cited above the A10398G (T114A) polymorphism in the NADH dehydrogenase subunit gene of the mitochondrial genome (Pezzotti et al, 2009). In consequence, a persistent dysfunction of mitochondrial respiratory chain is a source of ROS production in breast carcinoma cells.…”
Section: Causes and Consequences Of Persistent Oxidative Stress In Brmentioning
confidence: 99%